The Increase of nontuberculous mycobacteria Infection: Emphasis on Epidemiology, Risk Factors and Diagnostic Tools - Suryawati, B; Sari, Y; Saptawati, L (KnE Life Sciences, 2019)
Nontuberculous mycobacterium (NTM) is the species of mycobacteria other than Mycobacterium tuberculosis. In recent years, there is a significant increase in infection due to NTM species and disease caused by NTM infection increasingly becomes a health problem in countries with high prevalence or with a low prevalence of tuberculosis. NTM can cause various disease manifestations, but mainly it causes chronic pulmonary infections. Despite the rise of NTM infection, there is still limited information about NTM. This paper aims to elucidate the epidemiology of NTM, the risk factors of NTM infection, and the diagnostic methods used for the detection of NTM. Factors that have been identified for NTM infection including age, the presence of pulmonary diseases, immune-compromised conditions, and frequent exposure to NTM from the environment. Various techniques have been used to identify NTM from samples. The development of diagnostic tools such as the used of the massspectrometry assay and molecular techniques have enabled the detection of NTM worldwide and enable to identify into species level. However, in developing countries diagnosis of NTM is still challenging because of the limited diagnostic tools. In high prevalence tuberculosis countries, there is a growing concern that NTM has been diagnosed as tuberculosis. In addition, the possibility of co-infection of MTB and NTM in tuberculosis patients has also not been properly examined. These factors lead to misdiagnosis and inappropriate treatment for NTM infection. The knowledge about the species distribution of NTM, the risk factors, and the diagnostic methods is important to prevent the infection and provide accurate treatment of NTM infection.